Conflict Resolution Models In Muslim-Hindu Relations In India: AnAnalysis Of The Modi Administration's Policies (2014-2019) - Febrian Arif Pratama (Yayasan Cendekia Gagayunan Indonesia, 2025)
India, as a country with high ethnic and religious diversity, faces prolonged tensions between its two largest communities, Hindus and Muslims. This conflict is influenced by the British colonial legacy that created deep social and political divisions. After independence, even though India adopted a secular ideology, inter-religious tensions continued, especially after Narendra Modi took office as Prime Minister in 2014. Under his leadership, policies that support Hindu identity, such as the Citizenship Amendment Act (CAA) and the National Register of Citizens (NRC), among others, have fueled greater tensions between Hindus and Muslims. This article aims to analyze the steps taken by Modi in managing the conflict, focusing on the conflict resolution model he applied. Using a qualitative approach through literature study, this research adopts Barry R. Posen's Security Dilemma theory and Paul Brass's Elite Manipulation theory. The results of the study show that policies that prioritize Hindu identity have actually worsened social polarization and strengthened sectarian tensions, thwarting efforts at inclusive social reconciliation. This article suggests the need for a more equitable and inclusive policy approach in order to achieve sustainable reconciliation in India.